Red pitaya betacyanins protects from diet‐induced obesity, liver steatosis and insulin resistance in association with modulation of gut microbiota in mice. Issue 8 (August 2016) - Song, Haizhao; Chu, Qiang; Yan, Fujie; Yang, Yunyun; Han, Wen; Zheng, Xiaodong
Abstract: Background and Aim: Growing evidence indicates that gut microbiota contributes to obesity and its related metabolic disorders. Betacyanins possess free radical scavenging and antioxidant activities, suggesting its potential beneficial effects on metabolic diseases. The present study aimed to investigate the metabolic effect of red pitaya ( Hylocereus polyrhizus ) fruit betacyanins (HPBN) on high‐fat diet‐fed mice and determine whether the beneficial effects of HPBN are associated with the modulation of gut microbiota. Methods: Thirty‐six male C57BL/6J mice were divided into three groups and fed low‐fat diet (LFD), high‐fat diet (HFD), or high‐fat diet plus HPBN of 200 mg/kg for 14 weeks. Sixteen seconds rRNA sequencing was used to analyze the composition of gut microbiota. Results: Our results indicated that administration of HPBN reduced HFD‐induced body weight gain and visceral obesity and improved hepatic steatosis, adipose hypertrophy, and insulin resistance in mice. Sixteen seconds rRNA sequencing performed on the MiSeq Illumina platform (Illumina, Inc., San Diego, CA, USA) showed that HPBN supplement not only decreased the proportion of Firmicutes and increased the proportion of Bacteroidetes at the phylum level but also induced a dramatic increase in the relative abundance of Akkermansia at the genus level. Conclusions: Red pitaya betacyanins protect from diet‐induced obesity and its related metabolic disorders, which is associated with improved inflammatory status and modulation of gut microbiota, especially its ability to decrease the ratio of Firmicutes and Bacteroidetes and increase the relative abundance of Akkermansia . The study suggested a clinical implication of HPBN in the management of obesity, non‐alcoholic fatty liver disease, and type 2 diabetes.